Balinese Language as a Second Language in Early Children Development: Identification of the Affecting Factors - Yeni Lestari, Ni Gusti Ayu Made; Wiranata, I Gusti Lanang Agung (UNIB Press, 2025)
The utilization of the Balinese language among young children is an essential aspect to consider as it pertains to their ability to effectively engage with their surroundings. This qualitative investigation aims to identify the factors that impact the utilization of Balinese during early childhood. The study's participants consisted of five parents and two teachers of children in Group B2. The research method relied on interviews and documentation records, and the data were analyzed using taxonomic analysis. The findings of the study reveal that there are three primary factors that affect the use of Balinese in early childhood, which include language acquisition, language environment, and language learning. The environment, especially the family setting, plays the most crucial role in Balinese language usage. This research uncovered that children who belong to a specific caste and those who reside in suburban environments tend to utilize Balinese more frequently. The environment where children interact holds a significant impact on their chances of gaining experience in using Balinese.